Overexpression of OsGF14C enhances salinity tolerance but reduces blast resistance in rice - Dong, Jingfang; Li, Xuezhong; Ma, Yamei; Yang, Jianyuan; Chen, Jiansong; Yang, Wu; Zhou, Lian; Wang, Jian; Yang, TiFeng; Zhang, Shaohong; Zhao, Junliang; Liu, Qing; et al. (Frontiers in Plant Science, 2023)
High-salinity and blast disease are two major stresses that cause dramatic yield loss in rice production. GF14 (14-3-3) genes have been reported to play important role in biotic and abiotic stresses in plants. However, the roles of OsGF14C remain unknown. To understand the functions and regulatory mechanisms of OsGF14C in regulating salinity tolerance and blast resistance in rice, we have conducted OsGF14C-overexpressing transgenic experiments in the present study. Our results showed that overexpression of OsGF14C enhanced salinity tolerance but reduced blast resistance in rice. The enhanced salinity tolerance is related to the reduction of methylglyoxal and Na+ uptake instead of exclusion or compartmentation and the negative role of OsGF14C in blast resistance is associated with the suppression of OsGF14E, OsGF14F and PR genes. Our results together with the results from the previous studies suggest that the lipoxygenase gene LOX2 which is regulated by OsGF14C may play roles in coordinating salinity tolerance and blast resistance in rice. The current study for the first time revealed the possible roles of OsGF14C in regulating salinity tolerance and blast resistance in rice, and laid down a foundation for further functional study and crosstalk regulation between salinity and blast resistance in rice.